Long-Term Exposure to Traffic-Related Air Pollution and the Risk of Coronary Heart Disease Hospitalization and Mortality - Gan, Wen Qi; Koehoorn, Mieke; Davies, Hugh W.; Demers, Paul A.; Tamburic, Lillian; Brauer, Michael (Environmental health perspectives, 2011)
Background: Epidemiologie studies have demonstrated that exposure to road traffic is associated with adverse cardiovascular outcomes. Objectives: We aimed to identify specific traffic-related air pollutants that are associated with the risk of coronary heart disease (CHD) morbidity and mortality to support evidence-based environmental policy making. Methods: This population-based cohort study included a 5-year exposure period and a 4-year follow-up period. All residents 45-85 years of age who resided in Metropolitan Vancouver during the exposure period and without known CHD at baseline were included in this study (n = 452,735). Individual exposures to traffic-related air pollutants including black carbon, fine particles [aerodynamic diameter ≤ 2.5 μm (PM2.5)], nitrogen dioxide (NO₂), and nitric oxide were estimated at residences of the subjects using land-use regression models and integrating changes in residences during the exposure period. CHD hospitalizations and deaths during the follow-up period were identified from provincial hospitalization and death registration records. Results: An interquartile range elevation in the average concentration of black carbon (0.94 × 10⁻⁵/m filter absorbance, equivalent to approximately 0.8 ug/m 3 elemental carbon) was associated with a 3% increase in CHD hospitalization (95% confidence interval, 1-5%) and a 6% increase in CHD mortality (3-9%) after adjusting for age, sex, preexisting comorbidity, neighborhood socioeconomic status, and copollutants (PM2.5 and NO₂). There were clear linear exposure-response relationships between black carbon and coronary events. Conclusions: Long-term exposure to traffic-related fine participate air pollution, indicated by black carbon, may partly explain the observed associations between exposure to road traffic and adverse cardiovascular outcomes.